Pengaruh Edukasi Farmasi terhadap Tingkat Pengetahuan Minum Obat Pasien Diabetes Mellitus Tipe 2 - Mukriani, Mukriani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Background: Type 2 Diabetes Mellitus is a chronic disease that requires high compliance in long-term treatment. Low patient knowledge about how to take medication correctly is one of the main causes of non-compliance, which can worsen glycemic control and increase the risk of complications. Objective: This community service activity aims to evaluate the effect of pharmacy education on increasing the level of knowledge of Type 2 DM patients about how to take medication correctly and rationally. Method: The activity was carried out through a pre-test and post-test approach using leaflet media, direct counseling, and individual pharmacy consultations. The assessment was carried out on 30 Type 2 DM patients by comparing the results before and after education was given. Results: After pharmacy education, there was a significant increase in the respondents' knowledge scores. As many as 83% of patients were able to mention the dosage and rules for using the drug correctly after the intervention. Previously, most patients did not understand the importance of taking medication and the potential side effects. Discussion: These results indicate that pharmacy education is very effective in improving patient understanding of oral hypoglycemic medication. Education that is carried out communicatively and adjusted to the patient's condition has been proven to be able to change the patient's understanding and behavior in using drugs. This finding is in line with several previous studies that emphasize the important role of pharmacists in the management of Type 2 DM therapy. Conclusion: Pharmacy education has been proven to have a positive effect on increasing patient knowledge about taking medication properly. Similar interventions need to be implemented periodically and continuously as part of clinical pharmacy services in first-level health facilities.